Ethics - Its meaning, significance and concern for public administrators - Rasheed, Mazen Faris (1995)
"The author first briefly refers to problems involved in evolving a universal standard of ethical behaviour in Public Administration, and then discusses in some detail the need for ethics and the three different approaches prevailing in this regard. Demonstrating inadequacy of these approaches, he concludes with a brief discussion on preferable modes of internal and external control on Public Administration"
Keywords: Ethics - India; Civil service - India; Civil service